UPAYA MEMAKSIMALKAN PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR - Simangunsong, Mutiara (JURNAL PENA EDUKASI, 2018)
Abstract: Classroom action research in general aims to improve the quality of learning for fourth grade students of SD Negeri 010122 Sei Piring. specifically aimed at: (1) Efforts to Maximize the Use of Image Media to Increase Student Interests and Learning Outcomes with Cooperative Principal Material in Social Sciences Class IV SD Negeri 010122 Sei Piring district Pulau Rakyat academic year 2016/2017; (2) Describe the management of social studies learning by teachers. This classroom action research is carried out in 2 cycles, each cycle consisting of planning, implementing actions, observing and reflecting. This classroom action research was conducted in class IV SD Negeri 010122 Sei Piring, which amounted to 25 students. The subjects of this study were grade IV teachers and fourth grade students of SDN 010122 Sei Piring, data were collected through observation, interviews, tests, and documentation studies. Keywords: Images Media, Interests and Learning Outcomes Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas IV SDN 010122 Sei Piring. secara khusus bertujuan untuk: (1) Upaya Memaksimalkan Penggunaan Media Gambar Untuk Meningkatkan Minat dan Hasil Belajar Siswa Dengan Materi Pokok Koperasi Pada Pelajaran IPS Kelas IV SDN 010122 Sei Piring Kec. Pulau Rakyat TP. 2016/2017; (2) Mendeskripsikan pengelolaan pembelajaran IPS oleh guru. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Penelitian tindakan kelas ini dilaksanakan dikelas IV SDN 010122 Sei Piring yang berjumlah 25 orang siswa. Subjek penelitian ini adalah guru kelas IV dan siswa kelas IV SDN 010122 Sei Piring, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Kata kunci: Media Gambar, Minat dan Hasil Belajar